A note on iterative solutions of an iterative functional differential equation - Zhao, H. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.9 We propose an iterative method for solving the iterative functional differential equation x′ ′ (t) = λ_1x(t) + λ_2x^[2](t) + . . . + λ_nx^[n](t) + f(t).